SAHNYA PERKAWINAN MENURUT UNDANG-UNDANG NOMOR 1 TAHUN 1974 TENTANG PERKAWINAN DITINJAU DARI HUKUM PERJANJIAN - Trusto Subekti (Faculty of Law, Universitas Jenderal Soedirman, 2010)
Legal certainty is an indicator for a legal into good legal category, the fact about the validity of marriage has led a multi interpretation among the experts and the society, especially among Muslims. This is shown in the society members statement that